Seasonal changes in the sprint acceleration force-velocity profile of elite male soccer players - Jiménez-Reyes, P.; Garcia-Ramos, A.; Párraga-Montilla, J. A.; Morcillo-Losa, J. A.; Cuadrado-Peñafiel, V.; Castaño-Zambudio, A.; Samozino, P.; Morin, J. B. (The Journal of Strength and Conditioning Research, 2022)
This study aimed to describe the seasonal changes in the sprint force-velocity (Fv) profile of professional soccer players. The sprint Fv profile of 21 male soccer players competing in the first division of the Spanish soccer league was evaluated 6 times: preseason 1 (September 2015), in-season 1 (November 2015), in-season 2 (January 2016), in-season 3 (March 2016), in-season 4 (May 2016), and preseason 2 (August 2016). No specific sprint capabilities stimuli other than those induced by soccer training were applied. The following variables were calculated from the velocity-time data recorded with a radar device during an unloaded sprint: maximal force (F0), maximal velocity (v0), Fv slope, maximal power (Pmax), decrease in the ratio of horizontal-to-resultant force (DRF), and maximal ratio of horizontal-to-resultant force (RFpeak). F0 (effect size [ES] range = 0.83-0.93), Pmax (ES range = 0.97-1.05), and RFpeak (ES range = 0.56-1.13) were higher at the in-seasons 2 and 3 compared with both preseasons (p = 0.006). No significant differences were observed for v0, Fv slope, and DRF (p = 0.287). These results suggest that relevant Fv profile variables may be compromised (F0 more compromised than v0) toward the end of the competitive season when specific sprint stimuli are not systematically applied.